Geospatial Mapping of Smallholder Oil Palm Plantation in Tanah Laut Regency Using QGIS - Jaka Darma Jaya; Rizqie Mayasari (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Smallholder oil palm plantations play a crucial role in the Indonesian palm oil industry, but research on their spatial characteristics and performance at the district level is limited, as most previous studies tend to generalize plantation trends without utilizing local geospatial analysis. This study addresses this gap by using QGIS 3.32.1 to classify, map, and assess the status of smallholder oil palm plantations in Tanah Laut Regency, South Kalimantan. Plantations are categorized into productive and non-productive based on district-level BPS data, with a total planted area of ​​14,479 ha, consisting of 12,693 ha of productive land and 1,786 ha of non-productive land. Batu Ampar has the largest productive land (3,527 ha), while Tambang Ulang and Panyipatan have significant non-productive land, 328 ha and 300 ha, respectively, indicating the presence of immature plantations. Total production varied between 396–4,603 tons, with Batu Ampar, Jorong, and Tambang Ulang as the main contributors, while yield per hectare ranged from 435–620 kg, with Bati-Bati recording the highest yield. These findings confirm that plantation management practices determine productivity more than land area alone. This study presents an integrative method that combines spatial and statistical data, facilitates district-level plantation monitoring, and demonstrates that the use of open-source GIS tools such as QGIS offers a cost-effective, replicable approach that supports planning, policy, and sustainable development for smallholder farmers.